NPV at Risk Review on Investment Evaluation of Hotel Development in Block M Jakarta - Aroka Aryadeta (Institut Teknologi Sepuluh Nopember, 2017)
Hotel Grandhika Blok M Jakarta built in 2013 and started operation in early 2016. In terms of investment, the function of the building is not necessarily the best. Therefore it is necessary to do further study on the evaluation of hotel development, whether it remains operational as a hotel or there is a better investment alternative on the land of Grandhika Hotel Block M. The results of spreading questionnaires to five property experts consisting of academic and practitioners experts, are obtained the probability for hotel 100% optimists and 0% pesimists, Apartement 60% optimists and 40% pesimists, Offices 40% optimists and 60% pesimists. Then do the calculation Net Present Value (NPV). From NPV analysis obtained value NPV after 8 years for hotel NPV Rp. 7,788,146,628.49 , apartments NPVRp. 17,992,955,784.81 and officeNPV Rp. 6,852,663,146.56. For a maximum productivity analysis of the value of the property at the end of the investment period, so the utilization of land for the hotel will provide productivity of76.90%, for apartements provide productivity of 41.62% and office provide value of productivity of 18.16%. After obtained probability, productivity analysis and Net Present Value then taken decision by using decision tree method. The result is that the hotel as the best investment. From these results the best investment the investor can decide whether to continue operating the hotel or change functions the best alternative of the existing alternatives.